2004
DOI: 10.1249/01.mss.0000147628.78551.3b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Approaches to Structured Physical Activity Surveys for Adolescents

Abstract: Purpose-To compare the test-retest reliability, convergent validity, and overall feasibility/ usability of activity-based (AB) and time-based (TB) approaches for obtaining self-reported moderate-to-vigorous physical activity (MVPA) from adolescents.Methods-Adolescents (206 females and 114 males) completed two 3-d physical activity recalls using the AB and TB surveys, which contained identical lists of physical activities. The participants wore an MTI Actigraph ® accelerometer for the same period.Results-The TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
8

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 27 publications
2
123
0
8
Order By: Relevance
“…28 Weak but significant associations between questionnaires and accelerometer data have been found in other studies with adolescents, [29][30][31] particularly in young adolescents. 30 Good measurements of low and moderate physical activities, using self-reported means, have been shown to be the most difficult to obtain for both adults and adolescents.…”
Section: Validation Of the Ipaq In Adolescentsmentioning
confidence: 73%
“…28 Weak but significant associations between questionnaires and accelerometer data have been found in other studies with adolescents, [29][30][31] particularly in young adolescents. 30 Good measurements of low and moderate physical activities, using self-reported means, have been shown to be the most difficult to obtain for both adults and adolescents.…”
Section: Validation Of the Ipaq In Adolescentsmentioning
confidence: 73%
“…Dentre eles, 41 haviam analisado a reprodutibilidade "teste-reteste" e 58 a validade. Alguns estudos analisaram mais de um instrumento (n = 10) 16,17,18,19,20,21,22,23,24,25 e, nos estudos com análise de validade, 15 instrumentos foram comparados contra mais de um critério de referência -"padrão-ouro" 16,23,26,27,28,29,30,31,32,33,34,35 . Em função disso, nesta revisão, o "instrumento" será a unidade de análise e, por conseguinte, em algumas vezes os valores de "n" (ou o número de referências citadas) serão diferentes do número de estudos revisados (Figura 1).…”
Section: Resultsunclassified
“…Identificaram-se 52 instrumentos diferentes (42 questionários, 6 diários e 4 entrevistas estruturadas), mas apenas 11 haviam sido testados mais de uma vez 16,18,20,21,22,24,25,26,29,30,31,33,35,36,37,39,41,44,46,49,52,54,55,58,59,60,61,62,63,64,65,66,67 . A maioria destes instrumentos (33/52) 19,20,21,22,23,24,25,27,28,32,35,38,40,41,46,47,50,51,53,…”
Section: Resultsunclassified
“…Girls also completed a revised Three Day Physical Activity Recall (3DPAR) (Pate et al, 2003;McMurray et al, 2004) which indicated where they did PA (i.e., home/neighborhood, school, other outdoor public area, other, and community facilities). Community facilities included parks, playgrounds, recreation centers, churches, dance studios, and fields or gyms.…”
Section: Use Of Community Facilitiesmentioning
confidence: 99%